2023
DOI: 10.1155/2023/1287325
|View full text |Cite|
|
Sign up to set email alerts
|

Bioinspired Synthesis of Zinc Molybdate Nanoparticles: An Efficient Material for Growth Inhibition of Escherichia coli, Staphylococcus aureus, and Dye Remediation

Abstract: Zinc molybdate nanoparticles with molybdate are synthesized through green method with different salt precursors using Moringa oleifera leaf extract. Those nanoparticles had structural, vibrational, and morphological properties, which were determined by X-ray diffraction (XRD). The crystalline size of synthesized zinc molybdate was 24.9 nm. Fourier transform infrared (FTIR) spectroscopy and field emission scanning electron microscopy (FE-SEM) clearly showed the attachment of molybdate with ZnO. The synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%